Maskulinisasi ikan nila (Oreochromis niloticus) melalui pemberian propolis yang dicampur dalam pakan buatan - Tatalede, Putri A.; Sinjal, Hengky J.; Watung, Juliaan Ch.; Salindeho, Indra R.N.; Kalesaran, Ockstan J. (Universitas Sam Ratulangi, 2019)
This study was conducted to determine the optimal dose of propolis for male sex reversal in tilapia larvae through mixing in artificial feed. This research was carried out at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine Sciences, Sam Ratulangi University. The experimental fish was taken from Board of Freshwater Fisheries Aquaculture at Tatelu. As many as 4,000 individuals fish aging 5 days were acclimatized for 2 days in an aquarium measuring 60 x 40 x 40 cm. After the acclimatization process was terminated, the larvae density was set to 100 per aquarium. Furthermore, the fish were fed with treatment feed previously added with propolis with a dose of A (0 mL/kg of feed) as a control, B (0.9 mL/kg of feed), C (1.8 mL/kg of feed), D (2.7 mL/kg of feed) and t E (3.6 mL/kg of feed). Treatment feed was given to larvae twice a day for 28 days. The results showed that masculinization of tilapia using propolis mixed into artificial feed had a very significant effect on the percentage of male tilapia and survival. In this study treatment C (1.8 mL/kg of feed) and treatment D (2.7 mL/kg of feed) resulted in the highest percentage of male tilapia which was 81.33% and 88.00% respectively. This shows that the administration at 1.8 mL/kg in artificial feed has a very real and effective effect on masculinization.Keywords: Oreochromis niloticus, masculinization, sex reversal, propolis